(untitled) (New York, N.Y., 2005)
It has long been acknowledged that productivity growth is key to rising living standards and poverty reduction. This book comprises a coherent collection of studies of links between globalization and productivity growth. Chapters cover all aspects of firm entry to international markets including foreign direct investment, acquisition and arms length exports.
Keywords: Industrial productivity,Investment, foreign,International business enterprises,Globalization,Exports; Economic aspects